ANALISIS PEMBELAJARAN DARING SENI BUDAYA DAN PRAKARYA PADA SISWA KELAS 2 DI SDN KUTAMANEUH KABUPATEN SUKABUMI - Ninda Sumarlin; Irna Khaleda; Luthfi Hamdani Maula (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is focused on the description of the analysis result of the online learning process of cultural arts and crafts for the second-grade students of SDN Kutamaneuh, Sukabumi. The method used in writing the research in this article is a qualitative descriptive method with the case study. Data collection techniques used are observation, interviews and documentation. The author conducts the data collection instrument. The data analysis technique, which is used by Miles and Huberman, consists of data reduction, data presentation and conclusion or verification. The research subjects involved the students of class 2B students at SDN Kutamaneuh in the academic year 2020/2021 with the number of 36 students from 17 male students and 19 female students and teachers who teach all subjects who are involved in the learning process in the classroom 2B. The results of the research indicated that the online learning process of students continued to run well, even though online learning was not as productive as face-to-face learning. In the teaching and learning process, 7 important components included teachers, students, learning objectives, learning materials, learning methods, learning media, and learning evaluation. Those components remained in online learning even though in the teaching and learning process those components did not work optimally, for example, the lack of use of learning methods and media